Horta escolar para alfabetização cientifica e ecológica: possibilidades e desafios - RODRIGUES, Silvia Maria Pacheco (2024)
This work of conclusion of course presents the result of a research of qualitative nature for the directors of the schools surveyed and objectives: investigate the possibilities and challenges of using the school garden to scientific and ecological literacy; conduct survey on the existence of horta in public schools in the municipality of brief; see how schools have vegetable gardens to use in teaching and learning process; and investigate whether science teachers use gardens for science and ecological literacy. The survey was based on the principles of qualitative paradigm and as a tool for data collection adopted the questionnaire. The results indicated that despite the wealth of possibilities offered by the garden space in schools, it was noted that it is not exploited by teachers, in particular by the science teachers. Most of the school municipality of brief the garden does not exist, and in schools.